2019
DOI: 10.2174/1389200220666190725115503
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Serotonin Metabolism, Gut-Microbiota and the Gut-Brain Axis

Abstract: Background:: Serotonin (5-HT) has a pleiotropic function in gastrointestinal, neurological/psychiatric and liver diseases. The aim of this review was to elucidate whether the gut-microbiota played a critical role in regulating peripheral serotonin levels. Methods:: We searched for relevant studies published in English using the PubMed database from 1993 to the present. Results: : Several studies suggested that alterations in the gut-microbiota may contribute to a modulation of serotonin signalling. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 85 publications
(109 reference statements)
0
46
0
Order By: Relevance
“…Symptoms of some gastrointestinal functional disorders may be due to deregulation of CNS activity, dysregulation at the peripheral level (intestine), or a combination of both (brain-gut axis) by means of neuro-endocrine-immune stimuli. In addition, several studies have demonstrated the profibrogenic role of serotonin in the liver, showing that it works synergistically with platelet-derived growth factor in stimulating hepatic stellate cell proliferation [237].…”
Section: Aminoacids and Their Derived Hormonesmentioning
confidence: 99%
“…Symptoms of some gastrointestinal functional disorders may be due to deregulation of CNS activity, dysregulation at the peripheral level (intestine), or a combination of both (brain-gut axis) by means of neuro-endocrine-immune stimuli. In addition, several studies have demonstrated the profibrogenic role of serotonin in the liver, showing that it works synergistically with platelet-derived growth factor in stimulating hepatic stellate cell proliferation [237].…”
Section: Aminoacids and Their Derived Hormonesmentioning
confidence: 99%
“…Additionally, it was speculated that patients with diarrhoea-predominant IBS might present with higher plasma levels of serotonin due to an impaired re-uptake, while patients with constipation-predominant IBS might have lower postprandial plasma levels due to a disturbance of the serotonin release (Holtmann et al, 2017), indicating that an impaired serotonin signalling seems to be involved in the pathogenesis of IBS affecting intestinal motility. Furthermore, an association of serotonin transporter polymorphisms and psychiatric illnesses, frequent in patients with IBS, has been established (Cristina et al, 2019). Taking these results into account could help to explain why central neuromodulators such as antidepressants affecting the serotonin system are also useful to treat FGIDs (Drossman et al, 2018).…”
Section: Effect Of Ed Treatment On Fgids/ Fgid Symptoms In Patients With Edsmentioning
confidence: 99%
“…In rats, development of ECs begins in utero in the duodenum and reaches levels seen in adult rats by birth [83]. Interestingly, once the BBB has been established in developing animals, gut serotonin levels rise dramatically until SERT expression in intestinal epithelium increases in the postnatal period [84]. Enteric nervous tissue develops from invading vagal and sacral neural crest cells that differentiate into neurons and glia.…”
Section: Serotonin and Neurodevelopmentmentioning
confidence: 99%